The Role of the Circular Economy in Improving the Sustainability of the Creative Industry in Indonesia - Septien Dwi Savandha (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
This research aims to analyze the role of the circular economy in improving the sustainability of the creative industry in Indonesia. The background of the research departs from global problems related to high material consumption and waste, as well as the significant contribution of the creative sector to the national Gross Domestic Product (GDP). Although the concept of the circular economy is increasingly recognized internationally, its implementation in Indonesia's creative industry is still limited and partial. This study uses a qualitative approach with an exploratory case study design. The subjects of the study were 15 business actors in the fashion, crafts, and culinary subsectors in Jakarta, Bandung, Yogyakarta, and Surabaya. Data were collected through in-depth interviews, licensed employee questionnaires, participatory observations, and documentation studies, and were thematically analyzed. The results of the study show that the implementation of the circular economy in the creative sector is more focused on the use of residual materials, the use of recycled materials, and the replacement of environmentally friendly packaging. The main obstacles include cost limitations, lack of market incentives, and low consumer literacy. The findings also confirm variations across subsectors: fashion excels in the use of leftover fabrics, crafts in recycled materials, and culinary in plastic reduction. The implications of this study emphasize the importance of integrating circular principles into business strategies, employee education, and government policy support. This is expected to accelerate the transition to a more competitive, sustainable, and adaptive creative industry to global demands.